The evolution of primary care databases in UK: a scientometric analysis of research output - Vezyridis, Paraskevas; Timmons, Stephen (BMJ Publishing Group, 2016)
Objective:To identify publication and citation trends, most productive institutions and countries, top journals, most cited articles and authorship networks from articles that used and analysed data from primary care databases (CPRD, THIN, QResearch) of pseudonymised electronic health records in UK. Methods: Descriptive statistics and scientometric tools were used to analyse a SCOPUS dataset of 1891 articles. Open access software was used to extract networks from the dataset (Table2Net), visualise and analyse co-authorship networks of scholars and countries (Gephi) and, density maps (VOSviewer) of research topics co-occurrence and journal co-citation. Results: Research output increased overall at a yearly rate of 18.65%. While medicine is the main field of research, studies in more specialised areas include biochemistry and pharmacology. Researchers from UK, USA and Spanish institutions have published the most papers. Most of the journals that publish this type of research and most cited papers come from UK and USA. Authorship varied between 3-6 authors. Keyword analyses show that smoking, diabetes, cardiovascular diseases and mental illnesses, as well as medication that can treat such medical conditions, such as non-steroid anti-inflammatory agents, insulin and antidepressants constitute the main topics of research. Co-authorship network analyses show that lead scientists, directors or founders of these databases are, to various degrees, at the centre of clusters in this scientific community. Conclusions: There is a considerable increase of publications in primary care research from electronic health records. The UK has been well placed at the centre of an expanding global scientific community, facilitating international collaborations and bringing together international expertise in medicine, biochemical and pharmaceutical research.